Pengaruh Risiko Pasar, Risiko Keuangan Dan Risiko Bisnis Terhadap Return Saham Perusahaan Tekstil Dan Garmen Yang Terdaftar Di Bursa Efek Indonesia (Periode 2019-2022) - Nani Septiana; Ardiansyah Japlani; Alamsyah (Jurnal Manajemen DIVERSIFIKASI, 2025)
The aim of this research is to determine the influence of market risk, financial risk and business risk on stock returns of textile and garment companies listed on the Indonesian Stock Exchange (2019-2022 period). This research manages financial report data for 4 years, namely from 2019-2022 according to what is needed. This data is seen through company financial reports published by the Indonesian Stock Exchange (BEI) and tested using E-views 10. Based on tests carried out by researchers using data analysis techniques using analytical requirements testing (descriptive statistical analysis), classical regression assumption requirements testing (autocorrelation test, heteroscedasticity test and multicollinearity test), as well as hypothesis testing using panel data regression models and (Test t, the significant F test and the coefficient of determination test R2) found that the only variables that had a significant influence on stock returns were market risk and business risk variables, while the financial risk variables did not influence and were not significant on stock returns. Likewise for the simultaneous test which has been carried out based on the calculated F table or F-statistics of 0.987735 with a significance value of 0.0732981 which means > 0.05 so Ha is accepted and it can be concluded that Market Risk, Financial Risk and Business Risk together has no effect on stock returns.